2018
DOI: 10.1016/j.paid.2018.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Why does socially prescribed perfectionism place people at risk for depression? A five-month, two-wave longitudinal study of the Perfectionism Social Disconnection Model

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 40 publications
0
16
0
3
Order By: Relevance
“…This emphasis is also reflected in empirical research on the perfectionism social disconnection model which is centered around the notion that perfectionism renders people vulnerable to alienation and isolation from other people through a variety of mechanisms and processes (see Hewitt et al, 2017). There is increasing empirical support for elements of this model (e.g., Magson, Oar, Fardouly, Johnco, & Rapee, 2019; Smith, Sherry, McLarnon, et al, 2018).…”
mentioning
confidence: 99%
“…This emphasis is also reflected in empirical research on the perfectionism social disconnection model which is centered around the notion that perfectionism renders people vulnerable to alienation and isolation from other people through a variety of mechanisms and processes (see Hewitt et al, 2017). There is increasing empirical support for elements of this model (e.g., Magson, Oar, Fardouly, Johnco, & Rapee, 2019; Smith, Sherry, McLarnon, et al, 2018).…”
mentioning
confidence: 99%
“…They reported that social anxiety mediated the relationship between perfectionistic self-presentation and depression. Additionally, Smith et al (2018) studied a nonclinical sample of university-aged adults using a 5-month, two-wave longitudinal design. These authors found that socially prescribed perfectionism indirectly predicted depression symptoms 5 months later through interpersonal discrepancies (i.e., viewing oneself as falling short of others’ expectations) and social hopelessness (i.e., negative expectations concerning future interpersonal relationships).…”
Section: Evidence Of the Relevance Of Perfectionism To Depressionmentioning
confidence: 99%
“…The PSDM has mostly been supported by research regarding perfectionistic concerns but not perfectionistic standards (Smith et al, 2017; Smith et al, 2018). For example, Gilman et al (2011) found that adaptive perfectionists (corresponding to individuals having high perfectionistic standards) were associated with higher levels of positive interpersonal relationships than maladaptive perfectionists (corresponding to those with high perfectionistic concerns) or nonperfectionists.…”
Section: Perfectionism and The Social Disconnection Modelmentioning
confidence: 99%
“…Also, little research has investigated the role of perfectionism in cognitive appraisals of family’s attitudes and behaviors toward them. Existing research focused on interpersonal discrepancies in specific populations such as anxious individuals (e.g., Laurenti et al, 2008; Smith et al, 2018), with none targeting perceived family acceptance.…”
Section: Perceived Family Acceptance and Bidirectional Relations With...mentioning
confidence: 99%